Variants in or near KITLG, BAK1, DMRT1, and TERT-CLPTM1L predispose to familial testicular germ cell tumour - Kratz, Christian P (2011)
BACKGROUND: Familial testicular germ cell tumours (TGCTs) and bilateral TGCTs comprise 1–2% and 5% of all TGCTs, respectively, but their genetic basis remains largely unknown. AIM: To investigate the contribution of known testicular cancer risk variants in familial and bilateral TGCTs. METHODS AND RESULTS: The study genotyped 106 single nucleotide polymorphisms (SNPs) in four regions (BAK1, DMRT1, KITLG, TERT-CLPTM1L) previously identified from genome-wide association studies of TGCT, including risk single nucleotide polymorphisms (SNPs) rs210138 (BAK1), rs755383 (DMRT1), rs4635969 (TERT-CLPTM1L) in 97 cases with familial TGCT and 22 affected individuals with sporadic bilateral TGCT as well as 871 controls. Using a generalised estimating equations method that takes into account blood relationships among cases, the associations with familial and bilateral TGCT were analysed. Three previously identified risk SNPs were found to be associated with familial and bilateral TGCT (rs210138: OR 1.80, CI 1.35 to 2.41, p = 7.03×10(−5); rs755383: OR 1.67, CI 1.23 to 2.22, p=6.70×10(−4); rs4635969: OR 1.59, CI 1.16 to 2.19, p=4.07×10(−3)). Evidence for a second independent association was found for an SNP in TERT (rs4975605: OR 1.68, CI 1.23 to 2.29, p=1.24×10(−3)). Another association with an SNP was identified in KITLG (rs2046971: OR 2.33, p=1.28×10(−3)); this SNP is in high linkage disequilibrium (LD) with reported risk variant rs995030. CONCLUSION: This study provides evidence for replication of recent genome-wide association studies results and shows that variants in or near BAK1, DMRT1, TERT-CLPTM1L, and KITLG predispose to familial and bilateral TGCT. These findings imply that familial TGCT and sporadic TGCT share a common genetic basis.